Gene Flow Happens. Issue 1 (2nd January 2014) - Yoder, Anne D.
<x xml:space="preserve">Abstract</x> Debate over what is a species was already considered old hat when Darwin wrote his seminal abstract (as he called it) more than 150 years ago.1 Endless papers, workshops, and symposia have been presented in an effort to "solve" the species problem. Yet, here we are, at it again. Has there been any progress? I believe that there has been, and that among the many advances enabled by the genomics revolution, progress on species concepts and species recognition is among them. To quote Feder and colleagues, 2 we are on the brink of a "unified theory of speciation genomics."